Copolymer compound, resin composition
Patent Information
- Application Number
- CN202580021498.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Priority Date
- 2024-03-29
- Filing Date
- 2025-03-28
- Publication Date
- 2026-10-16
AI Technical Summary
另一方面,如果向片赋予柔软性则具有操作性恶化的倾向
[0049]根据本发明,可以提供在添加于树脂组合物时,可以兼有室温下的操作性、高温压缩性和再加工性的共聚物化合物。
Smart Images

Figure CN122935569A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to copolymer compounds and resin compositions comprising the copolymer compounds. Background Technology
[0002] In recent years, with the miniaturization and high performance of electrical equipment, there is a demand for material technologies that can efficiently dissipate the heat generated during operation. Heat from heat sources such as IC chips is dissipated through heat sinks, but in order to achieve efficient heat conduction between the heat source and the heat sink, a resin composition called a TIM (thermal interface material) is often sandwiched between the heat source and the heat sink.
[0003] TIM (Transformer Injector) is a resin composition that combines resin with a thermally conductive filler, often using a sheet-like material with a thickness corresponding to the gap between the heat source and the heat sink. In recent years, to broaden the tolerance range of TIM assembly tolerances relative to the gap, sheets with high compressibility have been required. Furthermore, if high loads are applied for high compression, the chip may break, thus requiring a flexible sheet. On the other hand, imparting flexibility to the sheet tends to degrade operability. As a means to resolve this trade-off between compressibility and operability, resin compositions comprising a matrix such as silicone resin, a phase change material (PCM), and a thermally conductive filler have been proposed.
[0004] For example, in Patent Document 1, an invention relating to a thermally conductive film that is film-like at room temperature, has good operability, and softens upon heating is disclosed, which is a thermally conductive film containing a specific non-flowing silicone resin, a wax with a melting point of 20 to 60°C, and a thermally conductive filler in a prescribed amount.
[0005] In Patent Document 2, as a composition that can be used as a thermal interface material for electronic devices, an invention related to a composition comprising a base material containing 4 to 60% by weight of an organosilicon resin and 0 to 35% by weight of an organosilicon polymer, 40 to 96% by weight of a thermally conductive filler, 0 to 5% by weight of a treatment agent, and 0 to 1% by weight of an antioxidant is disclosed.
[0006] In Patent Document 3, as a heat countermeasure component that absorbs and transfers heat generated by heat sources such as electronic components and suppresses the overheating of such heat sources, an invention related to a heat countermeasure component formed by coating an organosilicon elastomer filled with paraffin powder with a particle size of 250 μm or less and thermally conductive filler with an average particle size of 30 μm or less with a coating material is disclosed.
[0007] Patent Document 4 discloses an invention relating to a thermally softening, thermally conductive silicone grease composition containing, in a specified amount, an organosilicon wax with a melting point of 30 to 80°C, a specific organopolysiloxane, and a thermally conductive filler, used as a composition for the thermal boundary between a heat-generating electronic component and a heat-dissipating component such as a heat sink or metal casing.
[0008] Patent document 5 discloses an invention related to a heat sink that softens with heat, has good adhesion between the heating element and the heat sink, and has good thermal performance. The invention includes a polymer gel such as silicone gel, a compound that is solid or paste at room temperature and becomes liquid when heated, and a thermally conductive filler.
[0009] In Patent Document 6, a material comprising a phase change substance that softens near the operating temperature of the heat source, a polymer component, a substance that causes the phase change substance to soften at a temperature that changes, and a thermally conductive filler are described as a heat-conducting material that transfers heat generated by a heat source to a heat sink by undergoing a phase change at the operating temperature of the microprocessor.
[0010] Patent Document 7 discloses an invention relating to a thermally conductive sheet containing an adhesive component as a mixture of an organosilicon matrix and a hydrocarbon compound, and a thermally conductive filler, having a compression ratio of 15% or more at 80°C and 0.276 MPa, and exhibiting shape retention. Furthermore, it describes how this thermally conductive sheet ensures good thermal conductivity while maintaining a certain degree of flexibility during use, while also exhibiting good shape retention and reliability.
[0011] Existing technical documents
[0012] Patent documents
[0013] Patent Document 1: Japanese Patent Application Publication No. 2023-47991
[0014] Patent Document 2: Japanese Patent No. 4954475
[0015] Patent Document 3: Japanese Patent Application Publication No. 2012-102264
[0016] Patent Document 4: Japanese Patent No. 6436035
[0017] Patent Document 5: Japanese Patent No. 3712943
[0018] Patent Document 6: Japanese Patent Application Publication No. 2001-89756
[0019] Patent Document 7: International Publication No. 2022 / 070568 Summary of the Invention
[0020] The problem that the invention aims to solve
[0021] However, for sheets made of TIM, reprocessability is also required to improve the yield rate during installation. However, the phase change materials used in conventional TIM are not compatible with the matrix, especially silicone resin, and therefore lack the toughness of TIM. This results in poor reprocessability, such as easy breakage when peeling the sheet from the substrate and some sheet residue remaining on the substrate.
[0022] In addition, sheets made of TIM are required to have better operability at room temperature and compressibility at high temperatures.
[0023] Therefore, the present invention aims to provide copolymer compounds that, when added to resin compositions, can combine room-temperature workability, high-temperature compressibility, and reprocessability.
[0024] In addition, the present invention also addresses the issue of providing thermally conductive materials with excellent operability at room temperature and high-temperature compressibility in other aspects.
[0025] Methods for solving problems
[0026] Through in-depth research, the inventors discovered that the above-mentioned problems can be solved by copolymer compounds in which long-chain organic groups, organic groups with organosilicon skeletons, and organic groups with carbon-carbon unsaturated bonds are respectively incorporated into the side chains.
[0027] Furthermore, through in-depth research, the inventors discovered that by analyzing the T2 relaxation curve of pulsed NMR measured at 10°C using the solid echo method in a thermally conductive material containing polyorganosiloxane, a thermally softening compound, and a thermally conductive filler, the proportion of a1 obtained is greater than a certain value, thereby solving the problems in other aspects.
[0028] That is, the present invention provides the following [1] to
[14] .
[0029] [1] Copolymer compounds having the structure shown in the following formula (1).
[0030]
[0031] (In equation (1), X) 1 ~X 3 Each is an independent trivalent organogroup, Y 1 ~Y 3 Each is an independent divalent organic group, Z 1 Z is a monovalent organic group. 2 (where R is a hydrogen atom or a monovalent organic group, R is an independent monovalent organic group, W is a divalent organic group and contains one or more carbon-carbon double or triple bonds, k is a number between 16 and 33, n, m, o, r, and s are each a number greater than 1, and p and q are each a number greater than 0.)
[0032] [2] According to the copolymer compound described in [1], the W above contains one or more 1,1-vinylene or 1,2-vinylene.
[0033] [3] According to the copolymer compound described in [1] or [2], the above-mentioned X 1 ~X 3 It is a hydrocarbon group with 2 or more but less than 3 carbon atoms.
[0034] [4] The copolymer compound according to any one of [1] to [3], wherein the above-mentioned Y 1 ~Y 3 It contains ester or amide groups.
[0035] [5] In any one of the copolymer compounds [1] to [4], the above m, n, and o satisfy the following relationship (α).
[0036] m / (n+m+o)≥0.025 Equation (α)
[0037] [6] In any one of [1] to [5], the copolymer compounds described above, m, n, o, and r, satisfy the following relationship (β). r / (n+m+o)≥1.00 Equation (β)
[0038] [7] The copolymer compound according to any one of [1] to [6], Z 2 It is a monovalent organic group.
[0039] [8] A resin composition comprising any one of [1] to [7], a polyorganosiloxane having hydrogen atoms in its molecular backbone that are directly bonded to silicon atoms, a catalyst, and a thermally conductive filler.
[0040] [9] The resin composition according to [8] further comprises a polyorganosiloxane having carbon-carbon double bonds in its molecular backbone.
[0041]
[10] According to the resin composition of [8] or [9], the thermally conductive filler is selected from at least one of metals, inorganic hydroxides, inorganic oxides, inorganic nitrides, carbon fibers, graphite and diamond.
[0042]
[11] In any one of the resin compositions according to [8] to
[10] , the content of the copolymer compound is 10 parts by mass or more relative to 100 parts by mass of polyorganosiloxane (X) contained in the resin composition.
[0043]
[12] A thermally conductive sheet is formed from a cured product of the resin composition described in any one of [8] to
[11] , wherein the thickness of the thermally conductive sheet is 0.05 mm or more and 5 mm or less.
[0044]
[13] According to the thermally conductive sheet of
[12] , at least one of the thermally conductive fillers has an anisotropic shape, and the thermally conductive filler having the anisotropic shape is oriented within the thermally conductive sheet.
[0045]
[14] A thermally conductive material is a thermally conductive material comprising a polyorganosiloxane, a thermally softening compound and a thermally conductive filler. When the T2 relaxation curve of the pulsed NMR obtained by measuring the above thermally conductive material at 10°C by solid echo method is analyzed by least squares fitting of the function shown in the following formula (12), the proportion of a1 obtained is more than 10%.
[0046]
[0047] (In equation (12), a1, a2, and a3 are the intensity ratios of each relaxation component such that a1 + a2 + a3 = 100%, t1, t2, and t3 are the T2 relaxation times of each relaxation component and t1 < t2 < t3, and x is the observation time in the relaxation measurement of pulsed NMR.)
[0048] The effects of the invention
[0049] According to the present invention, copolymer compounds that, when added to a resin composition, can possess room-temperature workability, high-temperature compressibility, and reprocessability can be provided.
[0050] Furthermore, in other aspects of the invention, thermally conductive materials with excellent operability at room temperature and high-temperature compressibility can also be provided. Attached Figure Description
[0051] Figure 1 A diagram illustrating the measuring machine used to determine thermal resistance. Detailed Implementation
[0052] [Copolymer Compounds]
[0053] The copolymer compounds of the present invention have the structure shown in formula (1).
[0054]
[0055] (In equation (1), X) 1 ~X 3 Each is an independent trivalent organogroup, Y 1 ~Y 3 Each is an independent divalent organic group, Z1 Z is a monovalent organic group. 2 (where R is a hydrogen atom or a monovalent organic group, R is an independent monovalent organic group, W is a divalent organic group and contains one or more carbon-carbon double or triple bonds, k is a number between 16 and 33, n, m, o, r, and s are each a number greater than 1, and p and q are each a number greater than 0.)
[0056] The copolymer compounds of the present invention can function as phase change materials when blended into resin compositions, providing good workability of the resin composition at room temperature (25°C) while improving compressibility at high temperatures (e.g., 60°C). Furthermore, the copolymer compounds of the present invention, by having the specific structure shown in formula (1), can improve the reprocessability of the resin composition, for example, preventing breakage of the composition when it is peeled from the substrate. In addition, low exudation also contributes to high reliability.
[0057] copolymer compounds via X 1 ~X 3 The main chain consists of sites with long-chain alkyl groups, sites with carbon-carbon double or triple bonds (hereinafter also referred to as "unsaturated carbon bonds"), and sites with organosilicon chains as branches.
[0058] The copolymer compound is a compound having units represented by formula (2), formula (3), and formula (4) in a molar ratio n:m:o. It should be noted that, in this specification, the unit represented by formula (2) is also referred to as a unit containing a long-chain alkyl group, the unit represented by formula (3) is also referred to as a unit containing an unsaturated carbon bond, and the unit represented by formula (4) is also referred to as a unit containing an organosilicon chain.
[0059]
[0060] X in equations (2) to (4) 1 ~X 3 Y 1 ~Y 3 Z 1 Z 2 R, k, p, q, r, s have the same meaning as in equation (1).
[0061] The copolymer compound, due to its presence of units containing long-chain alkyl groups, exhibits crystallinity and thus possesses a certain melting point. Therefore, it is in an unmelted state at room temperature but melts at high temperatures. As a result, resin compositions containing copolymer compounds and sheets formed from these compositions are considered to have good workability at room temperature and high compressibility at high temperatures. Furthermore, the copolymer compound, by having units containing unsaturated carbon bonds, with these unsaturated carbon bonds acting as crosslinking groups, reacts with polyorganosiloxanes (A) to form crosslinks, thus readily compatibility with polyorganosiloxanes, particularly polyorganosiloxane (A), resulting in improved toughness and reprocessability of the resin composition. Further, the copolymer compound, by having units containing silicone chains, readily compatibility with polyorganosiloxanes and their cured forms, improving dispersibility. In addition, the presence of silicone chains in the side chains also contributes to reduced exudation and further improved compressibility at high temperatures.
[0062] X in copolymer compounds 1 ~X 3 Each is an independent trivalent organogroup. X 1 ~X 3 It can contain heteroatoms such as oxygen, nitrogen, and sulfur atoms, but preferably does not contain heteroatoms. That is, X 1 ~X 3 Preferably, each component is an independent hydrocarbon group. This hydrocarbon group can be an aliphatic hydrocarbon group or an aromatic hydrocarbon group, but is more preferably an aliphatic hydrocarbon group.
[0063] X 1 ~X 3 Preferably, each hydrocarbon group is a trivalent hydrocarbon group with 2 or more but less than 6 carbon atoms, and more preferably, it is a hydrocarbon group with 2 or more but less than 3 carbon atoms. The hydrocarbon group can be a saturated hydrocarbon group or an unsaturated hydrocarbon group, but it is preferred to be a saturated hydrocarbon group.
[0064] X 1 ~X 3 Further preferred are groups that are each independently represented by the following formula (5) or (6). X is particularly preferred. 1 The group represented by formula (5), X 2 and X 3 The group is shown in formula (6).
[0065]
[0066] (In equations (5) and (6), 1 represents the bonding bonds that bind to the atoms of the main chain of the copolymer compound. 2 and 3 is related to Y 1 Y 2 Or Y 3(The bond of the combination)
[0067] Y 1 ~Y 3 Each is an independent divalent organogroup. Y 1 ~Y 3 Preferably, each organogroup is an organogroup having 1 or more and 10 or fewer carbon atoms, and more preferably, an organogroup having 1 or more and 6 or fewer carbon atoms. 1 ~Y 3 It may contain heteroatoms such as oxygen atoms, nitrogen atoms, and sulfur atoms, preferably oxygen atoms or nitrogen atoms, and more preferably oxygen atoms.
[0068] More specifically, Y 1 ~Y 3 Preferably, each of the groups is a divalent organic group containing an ester group or an amide group, and more preferably, an organic group containing an ester group.
[0069] Among them, Y 1 ~Y 3 Further preferred groups are each independently represented by the following formula (7) or (8). Y is particularly preferred. 1 The group represented by formula (7), Y 2 and Y 3 The group is shown in formula (8).
[0070]
[0071] In equations (7) and (8), 4 represents the bonding bonds that attach to the atoms of the main chain of the copolymer compound. 5 is a bonding bond that binds to the atoms of the side chains constituting the copolymer compound. Ra in formula (8) is an alkylene group having 1 or more and 10 or less carbon atoms, preferably an alkylene group having 1 or more and 4 or less carbon atoms.
[0072] Z 1 It is a monovalent organogroup. This organogroup is preferably composed of 1 or more but less than 10 carbon atoms, more preferably 1 or more but less than 4 carbon atoms. 1 It can contain heteroatoms such as oxygen, nitrogen, and sulfur atoms, but preferably does not contain heteroatoms. That is, Z 1 Preferably, it is a hydrocarbon group. The hydrocarbon group can be an aliphatic hydrocarbon group or an aromatic hydrocarbon group, but it is preferably an aliphatic hydrocarbon group.
[0073] Z 1 Preferably, the hydrocarbon group has 1 or more but less than 10 carbon atoms, and more preferably, it has 1 or more but less than 4 carbon atoms. The hydrocarbon group can be a saturated hydrocarbon group or an unsaturated hydrocarbon group, but it is preferred to be a saturated hydrocarbon group.
[0074] Among them, Z 1Preferably, each component is an alkyl group, more preferably an alkyl group having 1 or more but less than 4 carbon atoms. The alkyl group can be straight-chain or branched. Furthermore, Z 1 Methyl is further preferred.
[0075] Z 2 It can be a hydrogen atom or a monovalent organic group. Z 2 Preferably, it is a monovalent organogroup. In Z... 2 When Z is a monovalent organic group, 2 It can be related to Z 1 The same organic group can also be Z 1 Different organic groups, but preferably with Z 1 Same organic group.
[0076] Regarding Z 2 The monovalent organic group in it, due to as in the above regarding Z 1 As stated in the records, therefore detailed explanations are omitted.
[0077] In formula (1), k is the number of methylene (-CH2-) groups, which is 16 or more and 33 or less. By making k within such a range, the copolymer compound has a certain melting point, which makes the resin composition have good workability at room temperature, while improving the compressibility at high temperature, and further improving the reprocessability. k is preferably 16 or more and 30 or less, more preferably 17 or more and 25 or less.
[0078] It should be noted that in equation (1), the formation is related to Y. 1 The long-chain alkyl portion, i.e., the "-(CH2)k-" portion, exists in multiple forms depending on the number of n. k is the average value of the multiple "-(CH2)k-" portions.
[0079] In equation (1), Y 2 The W group is a divalent organic group with one or more unsaturated carbon bonds. This organic group preferably has 1 or more but less than 10 carbon atoms, more preferably 1 or more but less than 4 carbon atoms. W may have heteroatoms such as oxygen, nitrogen, and sulfur atoms, but preferably does not. That is, W is preferably an unsaturated hydrocarbon group. It is preferable that this unsaturated hydrocarbon group is an unsaturated aliphatic hydrocarbon group.
[0080] W is preferably an unsaturated hydrocarbon group with 1 or more but less than 10 carbon atoms, and more preferably an unsaturated hydrocarbon group with 1 or more but less than 4 carbon atoms. The unsaturated carbon bond can be either a reactive double bond or a reactive triple bond, but a reactive double bond is preferred.
[0081] Wherein, W further preferably contains one or more 1,1-vinylene or 1,2-vinylene, even more preferably contains one or more 1,1-vinylene, even more preferably contains one 1,1-vinylene, and particularly preferably contains 1,1-vinylene.
[0082] In equation (1), Y 3 Combined -(SiO) 4 / 2 ) p -(SiRO 3 / 2 ) q -(SiR2O 2 / 2 ) r -(SiR3O 1 / 2 ) s The - portion consists of organosilicon chains. Generally, as shown below, SiR3O 1 / 2 The part is called the M unit, SiR2O 2 / 2 The part is called the D unit, SiRO 3 / 2 The part is called the T unit, SiO 4 / 2 The part is called the Q unit.
[0083]
[0084] The organosilicon chain in formula (1) has SiR3O 1 / 2 (M unit), SiR2O 2 / 2 (D unit), which can have SiRO as needed. 3 / 2 (T unit) and SiO 4 / 2 Any or both of the (Q units). SiR3O in the organosilicon chain. 1 / 2 (M unit), SiR2O 2 / 2 (D unit), SiRO 3 / 2 (T unit), SiO 4 / 2 The arrangement of (Q units) is not particularly restricted. In equation (1), p, q, r, and s each represent SiO₂. 4 / 2 (Q unit), SiRO 3 / 2 (T unit), SiR2O 2 / 2 (D unit), SiR3O 1 / 2 The number of (M units).
[0085] It should be noted that SiR3O 1 / 2 (M unit) is monovalent and represents the terminal portion of the organosilicon chain. SiR₂O 2 / 2 (D unit) is divalent and represents the linear portion of the organosilicon chain. SiRO 3 / 2 The (T unit) is trivalent, with each of the three oxygen atoms bonding with any other unit to form a branched structure. SiO 4 / 2The (Q unit) is tetravalent, with each of the four oxygen atoms combining with any one of the units to form a branched structure.
[0086] Equation (1) and Y 3 In the combined organosilicon chain, R is a monovalent organogroup. This organogroup preferably has 1 or more but less than 10 carbon atoms, more preferably 1 or more but less than 4 carbon atoms. R may have heteroatoms such as oxygen, nitrogen, and sulfur atoms, but preferably does not. That is, R is preferably a hydrocarbon group. This hydrocarbon group can be an aliphatic hydrocarbon group or an aromatic hydrocarbon group, but is preferably an aliphatic hydrocarbon group.
[0087] R is preferably a monovalent hydrocarbon group having 1 or more and 10 or less carbon atoms, more preferably a hydrocarbon group having 1 or more and 4 or less carbon atoms. This hydrocarbon group can be a saturated hydrocarbon group or an unsaturated hydrocarbon group, but is preferably a saturated hydrocarbon group. R is preferably an alkyl group having 1 or more and 4 or less carbon atoms, and is preferably selected from at least one of methyl and butyl. Furthermore, in a molecule, more than 50% of the plurality of Rs are methyl, more preferably more than 80% are methyl, and even more preferably more than 90% are methyl.
[0088] In equation (1), m, n, and o preferably satisfy the relationship of equation (α) below.
[0089] m / (n+m+o)≥0.01 Equation (α)
[0090] If m / (n+m+o) is 0.01 or more as described above, the reprocessability of the resin composition is easily improved. It should be noted that m / (n+m+o) is an indicator of the proportion of units containing unsaturated carbon bonds in the copolymer compound of formula (1), and a value of a certain value or more is effective in improving the reprocessability of the present invention.
[0091] From this perspective, m / (n+m+o) is more preferably 0.015 or more, further preferably 0.025 or more, even more preferably 0.04 or more, and even more preferably 0.1 or less, and more preferably 0.08 or less.
[0092] In the copolymer compound of formula (1), r is a number of 1 or more. r is preferably 5 or more and 200 or less, more preferably 10 or more and 150 or less, and even more preferably 30 or more and 100 or less. If r is within the above range, the compressibility of the resin composition is easily improved. In addition, by having r within the above range, exudate is also easily reduced.
[0093] Furthermore, m, n, o, and r in equation (1) preferably satisfy the relationship of equation (β) below.
[0094] o r / (n+m+o)≥1.00 Equation (β)
[0095] If o When r / (n+m+o) is 1.00 or higher as mentioned above, the compressibility of the resin composition is easily improved. It should be noted that o r / (n+m+o) is an index of the proportion of the straight-chain portion (D unit) of the organosilicon chain in the copolymer compound of formula (1), and a value of a certain value is effective for the compressibility of the present invention.
[0096] From this perspective, o r / (n+m+o) is more preferably 1.02 or more, even more preferably 1.05 or more, and even more preferably 10.0 or less, and more preferably 7.0 or less.
[0097] In the copolymer compound of formula (1), s is a number of 1 or more. s is preferably 1 or more and 10 or less, more preferably 1 or more and 5 or less, and even more preferably 1.
[0098] In the copolymer compound of formula (1), p is a number of 0 or more, preferably 0 or more and 5 or less, more preferably 0 or more and 1 or less, and even more preferably 0.
[0099] In the copolymer compound of formula (1), q is a number of 0 or more, preferably 0 or more and 5 or less, more preferably 0 or more and 1 or less, and even more preferably 0.
[0100] It should be noted that in equation (1), Y 3 The number of combined organosilicon chains varies depending on the number of o. The values of p, q, r, and s in equation (1) are obtained as the average values among the multiple organosilicon chains.
[0101] In formula (1), n, m, and o each correspond to the number of units containing long-chain alkyl groups, units containing unsaturated carbon bonds, and units containing organosilicon chains. From the viewpoint of ensuring good compressibility of the resin composition at high temperatures while improving reprocessability, these numbers are preferably as described below.
[0102] n is a number greater than or equal to 1, for example, greater than or equal to 5 and less than 1000, preferably greater than or equal to 10 and less than 500, more preferably greater than or equal to 50 and less than 300, and even more preferably greater than or equal to 100 and less than 250.
[0103] m is a number of 1 or more, preferably 2 or more and 70 or less, more preferably 3 or more and 50 or less, and even more preferably 5 or more and 40 or less.
[0104] o is a number of 1 or more, preferably 3 or more and 70 or less, more preferably 5 or more and 50 or less, and even more preferably 8 or more and 40 or less.
[0105] In equation (1), n, m, o, k, p, q, r, and s can be obtained through... 1 H-NMR, 29 The results were obtained by Si-NMR, size exclusion chromatography, etc., as detailed in the examples.
[0106] There are no particular limitations on the manufacturing method of the copolymer compound. Examples include methods for polymerizing monomers used to form units containing long-chain alkyl groups as shown in formula (2), monomers used to form units containing unsaturated carbon bonds as shown in formula (3), and monomers used to form units containing organosilicon chains as shown in formula (4). It should be noted that, in the following description, the monomers used to form units containing long-chain alkyl groups as shown in formula (2) are referred to as crystalline monomers, the monomers used to form units containing long-chain alkyl groups as shown in formula (3) are referred to as crosslinking monomers, and the monomers used to form units containing organosilicon chains as shown in formula (4) are referred to as organosilicon monomers.
[0107] Examples of such crystalline monomers include, for example, alkyl (meth)acrylates.
[0108] Examples of crosslinking monomers include, for instance, (meth)acrylates containing unsaturated carbon bonds, represented by (meth)acrylates containing isoprene groups, such as (meth)acrylates with the following formula (X).
[0109]
[0110] (In formula (X), R is a hydrogen atom or a methyl group, Z) 2 W has the same meaning as in equation (1), and Ra has the same meaning as in equation (8).
[0111] Furthermore, examples of the aforementioned organosilicon monomers include single-terminal (meth)acrylic acid-modified organosilicones, where the single end of the organosilicon chain is modified with (meth)acrylic acid. It should be noted that the term "(meth)acryloyl" is a concept encompassing both acryloyl and methacryloyl groups.
[0112] [Resin Composition]
[0113] The present invention also provides resin compositions containing the above-described copolymer compounds. The copolymer compounds are suitable for use in compositions containing silicone resins other than the copolymer compounds; therefore, it is preferable that the resin compositions of the present invention contain the above-described copolymer compounds and a polyorganosiloxane (hereinafter also referred to as polyorganosiloxane (X)) other than the copolymer compounds. It is preferable that the polyorganosiloxane (X) serves as the matrix resin in the resin composition.
[0114] The resin composition of the present invention, by comprising the above-mentioned copolymer compound, can improve workability, high-temperature compressibility and reprocessability.
[0115] The content of the copolymeric compound in the resin composition is not particularly limited, but it is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, relative to 100 parts by mass of polyorganosiloxane (X) contained in the resin composition. If the content of the copolymeric compound is 5 parts by mass or more, the workability, compressibility and reprocessability of the resin composition are easily improved.
[0116] Furthermore, from the viewpoint that the amount of exudate in the resin composition can be easily reduced, the content of the copolymer compound in the resin composition is, for example, 110 parts by mass or less, preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less, relative to 100 parts by mass of polyorganosiloxane (X).
[0117] That is, the content of the copolymeric compound in the resin composition is, for example, 5 or more and 110 or less of polyorganosiloxane (X) relative to 100 parts by mass, preferably 5 or more and 50 or less, more preferably 10 or more and 40 or less, and even more preferably 15 or more and 30 or less.
[0118] More specifically, the resin composition of the present invention preferably includes at least a polyorganosiloxane (hereinafter also referred to as "polyorganosiloxane (A)") having hydrogen atoms directly bonded to silicon atoms in its molecular backbone, as polyorganosiloxane (X). Furthermore, the resin composition of the present invention is preferably used as a thermally conductive resin composition, and preferably further includes a catalyst and a thermally conductive filler.
[0119] <Polyorganosiloxane (A)>
[0120] The polyorganosiloxane (A) has hydrogen atoms directly bonded to silicon atoms in its molecular backbone. Therefore, each molecule of polyorganosiloxane (A) has at least one silyl group (SiH) in its molecular backbone. The presence of SiH in the molecular backbone enhances its reactivity with copolymer compounds, thereby improving the reprocessability of the cured resin composition. The number of SiHs in each molecule of polyorganosiloxane (A) can be one or more. For the formation of a cross-linked structure in the cured product, polyorganosiloxane (A) preferably comprises a polyorganosiloxane having two or more SiHs per molecule. Polyorganosiloxanes having two or more SiHs per molecule can be used alone or in combination with polyorganosiloxanes having one or more SiHs.
[0121] Examples of polyorganosiloxanes (A) include methylhydrosiloxane-dimethylsiloxane copolymers, polymethylhydrosiloxanes, polyethylhydrosiloxanes, and methylhydrosiloxane-phenylmethylsiloxane copolymers. They may or may not contain SiH at the end.
[0122] Preferably, in the resin composition, as the polyorganosiloxane (X), in addition to the polyorganosiloxane (A), it further includes a polyorganosiloxane having carbon-carbon double bonds in its molecular backbone (hereinafter also referred to as polyorganosiloxane (B)). By including polyorganosiloxane (B), it is easier to form a cross-linked structure in the cured product, and reprocessability is easily improved.
[0123] Examples of polyorganosiloxanes (B) include, for instance, polyorganosiloxanes having alkenyl groups. Preferably, each molecule of a polyorganosiloxane has two or more alkenyl groups, and more preferably, alkenyl groups are present at both ends. Furthermore, polyorganosiloxanes having alkenyl groups are preferably polyorganosiloxanes having vinyl groups.
[0124] Examples of vinyl-terminated polyorganosiloxanes include vinyl-terminated polydimethylsiloxane, vinyl-terminated polyphenylmethylsiloxane, vinyl-terminated dimethylsiloxane-diphenylsiloxane copolymer, vinyl-terminated dimethylsiloxane-phenylmethylsiloxane copolymer, and vinyl-terminated dimethylsiloxane-diethylsiloxane copolymer.
[0125] When the resin composition contains polyorganosiloxane (A) and polyorganosiloxane (B), polyorganosiloxane (A) and polyorganosiloxane (B) become the matrix resin, and the matrix resin becomes an addition reaction curable resin.
[0126] The viscosity of the polyorganosiloxane (X) at 25°C is preferably 5 mPa·s or more and 1000 mPa·s or less, more preferably 30 mPa·s or more and 700 mPa·s or less, and even more preferably 50 mPa·s or more and 600 mPa·s or less.
[0127] It should be noted that the viscosity of the polysiloxane is preferably measured using a viscometer (BROOKFIELD rotational viscometer DV-E) with a rotor of spindle No. 14 at a rotation speed of 5 rpm and a measurement temperature of 25°C. When the polysiloxane comprises polysiloxane (A) and polysiloxane (B) as described above, it is preferable that the viscosity of their mixture at 25°C be within the aforementioned range; however, the viscosities of polysiloxane (A) and polysiloxane (B) at 25°C may each be within the aforementioned range individually.
[0128] (catalyst)
[0129] The catalyst contained in the resin composition is preferably used as a curing catalyst for the polyorganosiloxane (A) and copolymer compound, or for polyorganosiloxanes (A) and (B). Specifically, platinum-based catalysts, palladium-based catalysts, rhodium-based catalysts, etc., can be used, with platinum-based catalysts being preferred. The amount of curing catalyst mixed relative to the total mass of the addition-reaction curable polyorganosiloxane is typically 0.1 to 200 ppm, preferably 0.5 to 100 ppm.
[0130] Curing retarders can be incorporated into resin compositions. Known substances can be used as curing retarders, including, for example, alkyne compounds such as 1-ethynyl-1-cyclohexanol and 3,5-dimethyl-1-hexyn-3-ol, various nitrogen compounds such as tributylamine and tetramethylethylenediamine, organophosphorus compounds such as triphenylphosphine, oxime compounds, and organochlorine compounds. By containing curing retarders, the catalytic activity of the curing catalyst can be suppressed, thereby extending the shelf life and pot life of the resin composition.
[0131] The content of the curing delay agent in the resin composition is preferably 0.01 parts by mass and 2 parts by mass and less, more preferably 0.1 parts by mass and 1 part by mass and less, relative to 100 parts by mass of polyorganosiloxane (X).
[0132] The resin composition may further include polyorganosiloxanes other than the above-mentioned polyorganosiloxanes (A) and (B) (hereinafter also referred to as other polyorganosiloxanes) as polyorganosiloxane (X). Examples of other polyorganosiloxanes include, for example, dimethyl silicone oil, polyphenylmethylsiloxane, and other silicone oils.
[0133] The content of other polyorganosiloxanes in the resin composition, based on the total amount of polyorganosiloxanes (X), is, for example, 10% by mass or less, preferably 5% by mass or less, and more preferably 3% by mass or less.
[0134] Thermally conductive filler
[0135] The resin composition of the present invention preferably contains a thermally conductive filler as described above. By including a thermally conductive filler, the thermal conductivity and heat dissipation of the resin composition are improved.
[0136] The type of thermally conductive filler is not particularly limited, but is preferably selected from at least one of metals, inorganic hydroxides, inorganic oxides, inorganic nitrides, carbon fibers, graphite and diamond.
[0137] Examples of such metals include aluminum, copper, and nickel.
[0138] Examples of such inorganic hydroxides include aluminum hydroxide, calcium hydroxide, and magnesium hydroxide.
[0139] Examples of such inorganic oxides include iron oxide, zinc oxide, silicon oxide (silicon dioxide), aluminum oxide, magnesium oxide, titanium oxide, cerium oxide, and zirconium oxide.
[0140] Examples of such inorganic nitrides include silicon nitride, aluminum nitride, gallium nitride, chromium nitride, tungsten nitride, magnesium nitride, molybdenum nitride, lithium nitride, and boron nitride.
[0141] Examples of the aforementioned carbon fibers include pitch-based carbon fibers, PAN-based carbon fibers, fibers made by carbonizing resin fibers, and fibers made by graphitizing resin fibers.
[0142] The graphite used can be, for example, natural graphite or artificial graphite.
[0143] The diamond mentioned above can be, for example, as-grown particles, fragmented diamond particles obtained by breaking as-grown particles, or other diamond particles, or a combination of two or more of them. It should be noted that, generally, as-grown particles are crystalline diamond particles that maintain their shape at the time of synthesis without undergoing breaking or other processes, and have a polyhedral shape. Fragmented diamond particles are obtained by breaking crystalline diamond particles, and generally have an angular shape obtained through breaking.
[0144] These thermally conductive fillers can be used alone or in combination of two or more.
[0145] As a thermally conductive filler, from the viewpoint of easily improving thermal conductivity, it is preferable to include at least one of inorganic oxide and carbon fiber, more preferably at least one of alumina and carbon fiber, and even more preferably alumina.
[0146] Preferably, at least one type of thermally conductive filler has an anisotropic shape, and furthermore, the thermally conductive filler having an anisotropic shape (hereinafter also referred to as "anisotropic filler") is oriented within the thermally conductive sheet described later. By oriented the anisotropic filler within the thermally conductive sheet, the thermal conductivity is easily improved. More preferably, the anisotropic filler is oriented along the thickness direction of the thermally conductive sheet.
[0147] Examples of anisotropic fillers include fibrous materials and flake-like materials. Anisotropic fillers have a high aspect ratio, specifically exceeding 2, and preferably 5 or higher. By having an aspect ratio greater than 2, it is easier to orient the anisotropic filler in a single direction, such as the thickness direction, thereby improving the thermal conductivity of the heat-conducting sheet in that single direction. Furthermore, while there is no particular upper limit to the aspect ratio, it is practically 100.
[0148] It should be noted that the aspect ratio is the ratio of the length of the major axis of an anisotropic filler to the length of the minor axis. In fibrous materials, it refers to the fiber length / fiber diameter, while in flake materials, it refers to the length of the flake material along its major axis / thickness.
[0149] There are no particular limitations on the anisotropic filler, and materials such as carbon fiber and boron nitride mentioned above can be used, with carbon fiber being the preferred choice.
[0150] In this specification, the term "orientation" is specifically as follows.
[0151] When the anisotropic filler is a fibrous filler, it means that the proportion of the number of anisotropic fillers whose angle with the long axis of the fibrous filler is less than 30° relative to any direction (e.g., the thickness direction) within the thermally conductive sheet is greater than 50% relative to the total amount of anisotropic filler, and this proportion is preferably greater than 80%.
[0152] Furthermore, when the anisotropic filler is a flake-shaped filler, it means that the proportion of the number of anisotropic fillers whose angle with respect to any direction within the thermally conductive sheet is less than 30° is greater than the total amount of anisotropic filler, and this proportion is preferably greater than 80%.
[0153] Furthermore, when the anisotropic filler is neither fibrous nor flaky, it means that the proportion of anisotropic fillers whose angle with respect to any direction within the thermally conductive sheet is less than 30° is greater than 50% of the total amount of anisotropic filler, and this proportion is preferably greater than 80%.
[0154] Anisotropic fillers can be oriented using known methods, such as magnetic field orientation (or flow orientation) by applying a magnetic field to the composition before curing and or flow orientation (or flow orientation) by applying shear force to the composition before curing and orienting it in one direction. It should be noted that in the case of flow orientation, for example, the composition before curing is stretched flat while being coated with shear force using a rod coater, doctor blade, or other coating device, extruded, or discharged from a nozzle, forming a sheet (primary sheet) in which the anisotropic filler material is oriented along the surface direction. Furthermore, these primary sheets can be stacked to obtain a block-shaped oriented molded body, which is then cut along the orientation direction of the anisotropic filler material to orient it along the thickness direction.
[0155] In addition to anisotropic fillers, thermally conductive fillers may also contain non-anisotropic fillers. Non-anisotropic fillers are fillers whose shape is not substantially anisotropic, and which do not align with the prescribed direction even when anisotropic fillers are oriented in a prescribed direction, such as under the generation of magnetic field lines or the action of shear force.
[0156] The aspect ratio of the anisotropic filler is 2 or less, preferably 1.5 or less. This low aspect ratio allows the anisotropic filler to be easily positioned within the gaps between the anisotropic fillers when used in conjunction with anisotropic fillers, thus facilitating improved thermal conductivity. Furthermore, the thermally conductive filler can be a solitary anisotropic filler used without anisotropic fillers.
[0157] The average particle size of the thermally conductive filler is not particularly limited, but it is preferably 0.1 μm or more and 250 μm or less, more preferably 0.2 μm or more and 100 μm or less.
[0158] It should be noted that the average particle size can be measured, for example, using a "laser diffraction particle size distribution measuring device" manufactured by Horiba Manufacturing Co., Ltd., simply by setting the particle size (d50) at 50% of the cumulative volume as the average particle size.
[0159] The thermally conductive filler preferably contains two or more types of particles with different average particle sizes. If two or more types of particles with different average particle sizes are used, the particles with smaller average particle sizes will enter between the particles with larger average particle sizes, so that the thermally conductive filler is properly dispersed in the polyorganosiloxane, and the filling rate of the thermally conductive filler can be easily improved.
[0160] It should be noted that the resin composition can be identified as having two or more particles with different average particle sizes by the presence of two or more peaks in the particle size distribution of the thermally conductive filler.
[0161] The amount of thermally conductive filler relative to the total amount of the resin composition is preferably 60% by mass or more, more preferably 65% by mass or more, and even more preferably 70% by mass or more. If the amount of thermally conductive filler is above these lower limits, it is easier to improve the thermal conductivity of the resin composition. It should be noted that the upper limit of the amount of thermally conductive filler is not particularly limited, but relative to the total amount of the resin composition, it is, for example, 95% by mass or less.
[0162] (Other additives)
[0163] The resin composition of the present invention may contain, as needed, dispersants such as silane coupling agents, antioxidants, heat stabilizers, colorants, flame retardants, antistatic agents, and other additives commonly used in resin compositions.
[0164] <Cured product>
[0165] In this invention, a cured product of the resin composition obtained by curing the above-described resin composition can also be provided. This cured product can be formed by appropriately heating the resin composition, for example, in a predetermined shape such as a sheet.
[0166] The cured product can be used as a heat dissipation component. Heat dissipation components are used, for example, inside electronic devices. Heat dissipation components made from the cured product of the resin composition of the present invention have good thermal conductivity, thus ensuring high heat dissipation even under conditions of high heat generation when used inside electronic devices. Furthermore, this heat dissipation component exhibits excellent operability at room temperature and excellent compressibility at high temperatures. Moreover, it has low exudate content and excellent reliability as a finished product.
[0167] Heat dissipation components are disposed, for example, on electronic components to dissipate heat generated by the electronic components. Furthermore, the heat dissipation component of the present invention can be disposed and used in a manner that fills the gap between two opposing components. The two opposing components are preferably, for example, one being an electronic component and the other being a heat sink for releasing heat from the electronic component, a housing of an electronic device, a substrate, etc. The heat dissipation component can be used as a so-called TIM (thermal interface material).
[0168] Furthermore, the cured resin composition has excellent reprocessability, so even if the cured material is peeled off from the adherend for purposes such as exchanging the cured material, it can prevent the cured material from breaking and a portion of the cured material from remaining on the adherend.
[0169] When the cured resin composition is in sheet form, it can be used as a thermally conductive sheet as a sheet-like heat dissipation component. The thickness of the thermally conductive sheet is preferably 0.05 mm or more and 5 mm or less, more preferably 0.1 mm or more and 4.5 mm or less, and even more preferably 0.2 mm or more and 4 mm or less. If the thickness of the cured material is a certain value or greater, it is easier to achieve good thermal conductivity. Furthermore, if the thickness of the cured material is a certain value or less, it can be suitable for use in confined spaces, such as inside electronic devices.
[0170] [Thermal conductive materials]
[0171] In other aspects, the present invention also provides a thermally conductive material comprising a polyorganosiloxane (X), a thermally softening compound, and a thermally conductive filler. For this thermally conductive material, the proportion of a1 when the T2 relaxation curve of the pulsed NMR measured at 10°C by solid-state echo method is analyzed by least-squares fitting of the function shown in the following equation (12) is 10% or more.
[0172]
[0173] (In equation (12), a1, a2, and a3 are the intensity proportions of each relaxation component such that a1 + a2 + a3 = 100%, t1, t2, and t3 are the T2 relaxation times of each relaxation component, and t1 < t2 < t3. (x represents the observation time in the relaxation measurement of pulsed NMR.) For pulsed NMR devices, the T1 and T2 relaxation curves of hydrogen nuclei can be obtained. By analyzing these curves, the T1 and T2 relaxation times can be determined. Both follow the Bloembergen-Purcell-Pound formula (BPP formula) and vary according to the relevant time τc of molecular motion. Therefore, molecular motion can be analyzed using the T1 and T2 relaxation times.
[0174] However, the T1 relaxation time of the hydrogen nucleus is affected by spin diffusion and is also influenced by factors other than motion, so it is generally difficult to use the T1 relaxation time of the hydrogen nucleus for motion analysis.
[0175] On the other hand, the T2 relaxation time, being unaffected by spin diffusion, clearly reflects the mobility of molecules, and is therefore specifically used for the analysis of the mobility of materials and the segmentation and analysis of the mobile components in materials.
[0176] It is known that the T2 relaxation time has a monotonic correlation with the correlation time τc of molecular motion, meaning that materials with longer τc have shorter T2 relaxation times, and materials with shorter τc have longer T2 relaxation times. Since τc is the reciprocal of the frequency of molecular motion, there is a tendency for materials with lower mobility to have shorter T2 relaxation times, and materials with higher mobility to have longer T2 relaxation times.
[0177] As mentioned above, while kinematics can be discussed from the T² relaxation time, there are several methods for measuring the T² relaxation time. Solid-state echo methods are suitable for materials with low kinematics, i.e., materials with short T² relaxation times. For pulsed NMR, ringing occurs immediately after pulse irradiation due to electromagnetic force, making it difficult to directly observe the initial stage of the relaxation curve. Therefore, for direct observation, since the short relaxation components that decay during the dead time cannot be observed, echo observations such as solid-state echo methods are specifically used.
[0178] The pulse configuration of the solid-state echo method is represented by 90°x-τ-90°y. For this method, by not observing the relaxation that occurs immediately after excitation, but observing the echo induced by the second pulse, it is possible to observe, in effect, a very fast relaxation that decays during dead time.
[0179] On the other hand, for solid-state echo methods, the influence of magnetic field inhomogeneity is significant due to the observation of free relaxation. In materials with high diffusion coefficients, intensity attenuation caused by diffusion dominates, leading to a large discrepancy between the apparent T2 relaxation time and the actual T2 relaxation time. Therefore, solid-state echo methods are specifically used for observing components with short T2 relaxation times, i.e., components with low mobility.
[0180] It should be noted that in the above pulse configuration, 90°x refers to tilting the macroscopic spin in the rotating coordinate system by 90° along the x-axis, and 90°y refers to tilting the macroscopic spin in the rotating coordinate system by 90° along the y-axis. In addition, τ represents the delay time between two 90° pulses.
[0181] In equation (12), a1 quantitatively represents the amount of the component in the thermally conductive material in which molecular motion is most suppressed.
[0182] In the thermally conductive material of this invention, a proportion of a1 less than 10% indicates that there is a low percentage of components with suppressed molecular motion, signifying that the thermally softening compound cannot be sufficiently dispersed in the polyorganosiloxane (X). Therefore, high-temperature compressibility and room-temperature operability may become insufficient.
[0183] Considering the above points, the proportion of a1 is preferably 10.1% or more, more preferably 12% or more. Furthermore, the proportion of a1 is not particularly limited, for example, it is 30% or less, preferably 25% or less.
[0184] It should be noted that during pulsed NMR measurements at 10°C, the crystalline sites in the thermally softening compound crystallize, and molecular motion is suppressed. The thermally softening compound exhibits good compatibility with polyorganosiloxane (X) by possessing, for example, polyorganosiloxane sites. Therefore, if the thermally softening compound is incorporated into a thermally conductive material, the molecular motion of the crystalline sites in the thermally softening compound is suppressed, and the polyorganosiloxane (X) present around these crystalline sites also exhibits suppressed molecular motion due to its interaction with these crystalline sites.
[0185] On the other hand, when a heat-softening compound with crystalline sites is blended into a resin with poor compatibility with the compound, even if the molecular movement of the crystalline sites is suppressed, the molecular movement of the resin surrounding the crystalline sites will not be suppressed. This invention, through a blending design that suppresses molecular movement not only in heat-softening compounds with crystalline sites at low temperatures but also in polyorganosiloxanes (X), provides a material with a higher a1 than previously possible.
[0186] The thermally conductive material of the present invention may or may not be curable. That is, the thermally conductive material of the present invention is preferably composed of a composition comprising a polyorganosiloxane (X), a heat-softening compound and a thermally conductive filler, or a cured product thereof.
[0187] The above-mentioned pulse NMR measurement can be performed on any value before or after curing when the thermally conductive material is curable. It is preferred to perform the measurement according to the usage plan. When the material is curable, the thermally conductive material is preferably cured.
[0188] A heat-softening compound is a compound having crystalline sites that softens upon reaching a certain temperature. Specifically, a heat-softening compound is one that exhibits crystallinity at 10°C, but softens by losing its crystallinity upon reaching a certain temperature. The temperature at which it loses its crystallinity and softens is expressed as its melting point. The melting point of a heat-softening compound is, for example, 30°C or higher and 90°C or lower, preferably 35°C or higher and 80°C or lower, more preferably 40°C or higher and 60°C or lower, and even more preferably 42°C or higher and 58°C or lower.
[0189] The crystalline site in the heat-softening compound is not particularly limited, as long as it is a hydrocarbon site, preferably a straight-chain hydrocarbon site, and more preferably a straight-chain aliphatic saturated hydrocarbon site. The number of carbon atoms in the hydrocarbon site is not particularly limited as long as it can impart crystallinity to the heat-softening compound. If it is a straight-chain aliphatic saturated hydrocarbon site, it is, for example, 16 or more and 33 or less, preferably 16 or more and 30 or less, and more preferably 17 or more and 25 or less.
[0190] Thermosoftening compounds only need to further possess polyorganosiloxane sites. By possessing polyorganosiloxane sites, thermosoftening compounds are readily compatible with the polyorganosiloxane (X) that constitutes the matrix of the thermally conductive material, and thus readily suppress the overall molecular motion of the thermally conductive material.
[0191] Furthermore, the heat-softening compound preferably has a reactive site (reactive site) that is reactive to the polyorganosiloxane (X) constituting the matrix. By having a reactive site, the heat-softening compound can bind to the matrix, thus making it easier to suppress molecular mobility in the overall thermally conductive material. The reactive site is preferably a crosslinking group that crosslinks with the polyorganosiloxane (X). Examples of reactive sites include unsaturated hydrocarbon groups such as reactive double bonds and reactive triple bonds, but reactive double bonds are preferred. Details of the unsaturated hydrocarbon group are as described in the copolymer compounds above, and it is further preferred to include 1,1-vinylene or 1,2-vinylene.
[0192] Examples of heat-softening compounds include the aforementioned copolymer compounds, paraffin wax, ester wax, etc., with copolymer compounds being preferred. By using copolymer compounds as heat-softening compounds, the compatibility with polyorganosiloxanes (X) is improved, and the proportion of a1 can be easily adjusted to a certain level or higher.
[0193] The polyorganosiloxane (X) used in the thermally conductive material is any polyorganosiloxane other than heat-softening compounds; there is no particular limitation as long as it is a polyorganosiloxane constituting the matrix resin of the thermally conductive material. Specifically, it can be a curable polyorganosiloxane such as an addition-reaction curable polyorganosiloxane or a condensation-type polyorganosiloxane, or a non-curable polyorganosiloxane such as silicone oil. Among these, an addition-reaction curable polyorganosiloxane is preferred.
[0194] The addition-cured polyorganosiloxane is preferably composed of polyorganosiloxane (A) and polyorganosiloxane (B), as detailed above.
[0195] The content of the heat-softening compound in the thermally conductive material, as described in the above-described resin composition, is preferably 5 parts by mass or more, more preferably 10 parts by mass or more, and even more preferably 15 parts by mass or more, relative to 100 parts by mass of polyorganosiloxane (X). Furthermore, relative to 100 parts by mass of polyorganosiloxane (X), it is, for example, 110 parts by mass or less, preferably 50 parts by mass or less, more preferably 40 parts by mass or less, and even more preferably 30 parts by mass or less.
[0196] Furthermore, the thermally conductive filler in the thermally conductive material is described in detail in the above-described resin composition, and its specific description is omitted. Additionally, the content of the thermally conductive filler relative to the total amount of the thermally conductive material, as described above, is preferably 60% by mass or more, more preferably 65% by mass or more, even more preferably 70% by mass or more, and, for example, 95% by mass or less.
[0197] Thermally conductive materials may contain components other than the aforementioned polyorganosiloxane (X), heat-softening compounds, and thermally conductive fillers. For example, in the case where the polyorganosiloxane (X) is an addition-reaction curing compound, the presence of a catalyst is preferable. Furthermore, thermally conductive materials may contain curing retarders, or other additives besides catalysts and curing retarders. Details of these catalysts, curing retarders, and other additives are described above.
[0198] The thermally conductive material on other sides can be composed of a cured product as described above. Details of the cured product are as described in the cured product section of the above resin composition, and it is preferable to use it in sheet form, for example. When the thermally conductive material is used in sheet form, the thickness of the thermally conductive material is as described in the cured product section of the above resin composition.
[0199] In addition, thermally conductive materials can be used in solutions other than sheet form, and can be used in amorphous forms such as grease.
[0200] In addition, thermally conductive materials can be used as heat dissipation components, and the details of their uses are as described above, such as their use inside electronic devices.
[0201] Furthermore, the thermally conductive material in other aspects of the present invention is particularly preferably a cured product of a resin composition containing the above-mentioned copolymer compound.
[0202] Example
[0203] The present invention will be made clear hereby by providing specific embodiments and comparative examples. It should be noted that the present invention is not limited to the following embodiments.
[0204] [Copolymer Compounds]
[0205] The following substances were used as raw materials for synthesizing copolymer compounds.
[0206] (organosilicon monomers)
[0207] • A compound with a single-terminal methacrylic acid-modified organosilicon with a viscosity of 60 cSt at 25°C and the structure shown in formula (9).
[0208]
[0209] (Crystall monomer)
[0210] · Stearyl acrylate
[0211] (Cross-linked monomers)
[0212] Isoprene methacrylate (IPEMA)
[0213] (Initiator)
[0214] ·5wt% azo initiator toluene solution
[0215] (solvent)
[0216] Toluene
[0217] <Synthesis of Copolymer Compounds>
[0218] Organosilicon monomers, crystalline monomers, and crosslinking monomers were mixed in toluene and bubbled with N2 for more than 20 minutes. Heating was initiated, and after reaching 62°C, a 5 wt% toluene solution of an azo initiator was added. After heating and stirring at 62°C for 17 hours, the mixture was cooled, the solvent was removed by distillation, and then heated under vacuum at 150°C for 2 hours to synthesize PCM(E1) to PCM(E6) as copolymer compounds. The proportions of each raw material added are recorded in Table 1.
[0219] PCM(E1) to PCM(E6) are compounds having the structure of formula (1) above, and more specifically, have the structure shown in formula (10). The detailed structures of PCM(E1) to PCM(E6) are described in Tables 2 and 3.
[0220]
[0221] <Comparative Synthesis of Copolymer Compounds: PCM(C1)>
[0222] PCM(C1) was obtained by operating in the same manner as the synthesis of the copolymer compounds described above, without using crosslinking monomers. The proportions of each raw material added are listed in Table 1, as are those for PCM(E1) to PCM(E6).
[0223] PCM(C1) has the structure shown in equation (11).
[0224]
[0225] [Table 1]
[0226] [Table 2]
[0227] <PCMs other than copolymer compounds>
[0228] In addition to the copolymer compound, PCM (C1) was further used as a PCM (C2). Furthermore, detailed information about the structures of PCM (C1) and (C2) is described in Table 3.
[0229] ·PCM(C2) HS- 4100P, the melting point of polyalphaolefins produced by Fengguo Oil Refinery is 35℃.
[0230] [Table 3]
[0231] <Weight-average molecular weight>
[0232] The weight-average molecular weight (Mw) of the synthesized products (each PCM) was determined by size exclusion chromatography using THF as a solvent. It should be noted that the weight-average molecular weight (Mw) is a converted value from standard polystyrene.
[0233] <Melting Point>
[0234] The melting points of the synthetic products (each PCM) were determined by differential scanning calorimetry (DSC).
[0235] The temperature was changed at a rate of 10℃ / minute, from -20℃ to 100℃, then from -20℃ to 100℃. The peak temperature of the largest peak in the graph (temperature 1) obtained during the cooling process from 100℃ to -20℃ and the peak temperature of the largest peak in the graph (temperature 2) obtained during the second heating process from -20℃ to 100℃ were obtained. The average value of temperature 1 and temperature 2 was set as the melting point.
[0236] <Calculation of each structural parameter in equation (1)>
[0237] (Calculation of p, q, r, s)
[0238] The synthesized PCMs were determined in a solution containing 0.1% tetramethylsilane in deuterated chloroform. 29 Si NMR spectrum.
[0239] The peak of tetramethylsilane was set to 0 ppm, and the peaks near 6.5–9.0, 20–24, -55–-65, and -105–-115 ppm were assigned to (SiO1 / 2), (SiO2 / 2), (SiO3 / 2), and (SiO4 / 2), respectively. p, q, r, and s were determined using the following formula. However, when R is any of the methyl groups, the following formula is applied based on appropriate peak assignment when the peak positions differ.
[0240] When <SiO4 / 2> ≠ 0 p = 1 q = <SiO3 / 2> / <SiO4 / 2> r = s <SiO2 / 2> / <SiO1 / 2> s = p 3 q 2 When <SiO4 / 2> = 0 and <SiO3 / 2> ≠ 0 p = 0 q=1 r = s <SiO2 / 2> / <SiO1 / 2> s=2 q When <SiO4 / 2> = 0 and <SiO3 / 2> = 0 p = 0 q = 0 r = s <SiO2 / 2> / <SiO1 / 2> s=1 Wherein, <SiOx / 2> represents the integral value of the peak belonging to SiOx / 2.
[0241] (Calculation of k)
[0242] The synthesized PCMs were determined in a deuterated chloroform solution. 1 The H NMR spectra were determined based on appropriate peak assignments.
[0243] The following shows the case of PCM(E1).
[0244] k=(<4.0> / <0.9>+<1.6> / <0.9>+<1.3> / <0.9>) 3 / 2
[0245] Where <xx> represents the integral value of the peak with a apex near x.xppm.
[0246] (o (Calculation of r / (n+m+o))
[0247] The synthesized PCMs were determined in a deuterated chloroform solution. 1 The H NMR spectra were determined based on appropriate peak assignments.
[0248] The following shows the case of PCM(E1).
[0249] o r / (n+m+o)=(<0.1> / 6) / (<4.0> / 2)
[0250] m / (n+m+o)=(<0.1> / 6) / (<4.0> / 2)
[0251] Where <xx> represents the integral value of the peak with a apex near x.xppm.
[0252] (Calculation of m, n, o, and m+n+o)
[0253] As described above, the weight-average molecular weight Mw of each PCM was calculated by size exclusion chromatography using THF solvent.
[0254] m, n, and o were calculated using the following formula using Mw.
[0255] After defining P = m + n + o, [m] = m / P, [o] = o / P, m, n, and o were calculated using the following formulas (A) to (C).
[0256] m = [m] P ···Form (A)
[0257] n = (1 - [m] - [o]) P ···Form (B)
[0258] o = [o] P ··· Formula (C)
[0259] Here, [m] and [o] can be derived from each PCM. 1 The measured values of the H NMR spectrum are calculated using the following formula, and P is calculated using these measured values through the following formula (D).
[0260] [m]=(<4.81>+<4.76>) / 2
[0261] [o] = <0.53> / 2
[0262] P = Mw / ([m] Mlink+[o] Msil+(1-[m]-[o]) Mcryst)···Form (D)
[0263] in, Mlink: Formula weight derived from repeating units of cross-linked monomers Mcryst: The formula weight derived from the repeating unit of a crystalline monomer. Msil: The formula weight derived from the repeating unit of organosilicon monomers.
[0264] These values are those shown in the table in this embodiment, and can be determined by combining appropriate 1D, 2D, and multinucleus NMR spectroscopy methods.
[0265] [Examples 1-12, Comparative Examples 1-7]
[0266] Mix the thermally conductive filler, dispersant, silicone base agent, and PCM separately in their respective specified amounts in the sample tubular vial, gently mix by hand, and then use... (A trademark for a self-rotating-revolutionary hybrid machine) (Company-made) It was mixed twice at 1400 rpm / 30 sec. Then it was heated at 80°C for 30 minutes and then... The mixture was kneaded. After cooling to room temperature, a silicone curing agent was added for further processing. The mixture was kneaded and allowed to stand under vacuum for 5 minutes to remove air bubbles, resulting in a resin composition. The obtained resin composition was then sandwiched between a release film and sheeted using stretch rollers, and heated at 150°C for 1 hour to obtain a cured resin composition. It should be noted that the size and shape of the cured product were appropriately adjusted according to the various evaluation methods.
[0267] Tables 4 and 5 show the formulations of the resin compositions prepared in the various examples and comparative examples. It should be noted that decyltrimethoxysilane, as a silane coupling agent, was used as a dispersant, a vinyl-containing polyorganosiloxane as the organosilicon base, and an organohydrogen polysiloxane as the organosilicon curing agent. It should also be noted that a small amount of curing catalyst was included in the organosilicon base. Furthermore, alumina with an average particle size of 0.5 μm, 3 μm, and 10 μm was used as thermally conductive fillers.
[0268] (Change in elastic modulus)
[0269] The cured resin composition (thermally conductive material) molded into a 2mm thick sheet was cut to produce two rectangular test pieces, each 6mm long, 6mm wide, and 2mm thick. Then, a viscoelasticity measuring device (DVA200) was used. Using a shear test fixture (manufactured by the company), the elastic modulus was measured in the range of -10℃ to 70℃. The change in elastic modulus was then calculated using the following formula: where log is the common logarithm. It should be noted that in Comparative Examples 5 and 7, since thermally conductive materials could not be manufactured, the elastic modulus was not measured or evaluated.
[0270] Change in elastic modulus = log(measured value at 10℃) - log(measured value at 70℃)
[0271] The conditions for determining the elastic modulus are as follows.
[0272] Temperature range: -10~70℃
[0273] Heating rate: 10℃ / minute
[0274] Frequency: 10Hz
[0275] Strain: 0.01%
[0276] Furthermore, in Examples 1-6 and Comparative Examples 1-3, the elastic modulus was evaluated according to the following evaluation criteria.
[0277] A: 1.4 or above
[0278] B: 0.6 or higher and less than 1.4
[0279] C: 0.4 or higher and less than 0.6
[0280] D: Less than 0.4
[0281] Furthermore, in Examples 7-12 and Comparative Examples 4 and 6, the elastic modulus was evaluated according to the following evaluation criteria.
[0282] A: 1.4 or above
[0283] B: 1.2 or higher and less than 1.4
[0284] C: 1.0 or higher and less than 1.2
[0285] D: Less than 1.0
[0286] (elongation)
[0287] The cured resin composition, molded into a 2mm thick sheet, was processed into test pieces using a test piece die (stretching type 7 dumbbell shape, Polymer Instrument Co., Ltd.). Then, it was used... The universal testing apparatus (RTI1310, AND Corporation) was used to perform a tensile test at 25°C, and the elongation was calculated using the following formula.
[0288] Elongation (%) = ((distance between marks at fracture) - (distance between marks before tensile test)) / (distance between marks before tensile test)
[0289] Furthermore, the elongation was evaluated according to the following evaluation criteria. It should be noted that the measurement and evaluation of elongation were carried out in Examples 1-6 and Comparative Examples 1-2, but not in Examples 7-12 and Comparative Examples 4-7.
[0290] A: More than 230%
[0291] B: 165% or higher but less than 230%
[0292] C: 150% or more but less than 165%
[0293] D: Less than 150%
[0294] (Exudate volume)
[0295] The cured resin composition, molded into a sheet 3.5 mm thick, was cut into 20 mm × 1 mm squares to prepare test pieces T, and their weight was measured (weight 1). Each test piece T was clamped with a metal plate and compressed until it reached a thickness of 2 mm, and then heated at 150°C for 64 hours in this state. After heating, the test pieces were removed and their weight was measured (weight 2), and the exudate amount was calculated using the following formula.
[0296] Leakage amount = (weight 1 - weight 2) / (weight 1)
[0297] Furthermore, the amount of exudation was evaluated according to the following evaluation criteria. It should be noted that the measurement and evaluation of the amount of exudation were carried out in Examples 1-6 and Comparative Examples 1-3, but not in Examples 7-12 and Comparative Examples 4-7.
[0298] A: The exudate is below 0.3.
[0299] B: Exudate exceeding 0.3 but below 0.4
[0300] C: Exudate exceeding 0.4 but below 0.5
[0301] D: Exudation exceeds 0.5
[0302] (Thermal resistance)
[0303] Test pieces consisting of cured resin compositions molded into sheets 1.1 mm thick were used. Figure 1 The thermal resistance was measured using the thermal resistance measuring instrument shown in the figure by the following method.
[0304] For each sample, a 30mm × 30mm test piece S was prepared for this test. Each test piece S was then attached to a copper block 22 with a measuring surface of 25.4mm × 25.4mm and sides covered by heat insulation material 21, and clamped by an upper copper block 23. A pressure of 40psi (0.276MPa) was applied using a force sensor 26. Here, the lower copper block 22 is connected to a heater 24. Furthermore, the upper copper block 23 is covered by heat insulation material 21 and connected to a heat sink 25 with a fan. Next, the heater 24 was heated to a heat output of 25W, and after 10 minutes when the temperature reached a substantially stable state, the temperature (θ) of the upper copper block 23 was measured. j0 ), the temperature (θ) of the copper block 22 below j1 The thermal resistance of each sample was calculated using the following formula (a): (The heat generated by the heater (Q)). It should be noted that the temperature was adjusted to 80°C for each sample.
[0305] Thermal resistance = (θ) j1 -θ j0 ) / Q ··· Formula (a)
[0306] In equation (a), θ j1 θ represents the temperature of the copper block 22 below. j0 Q represents the temperature of the copper block 23 above, and Q represents the heat generated.
[0307] Furthermore, the thermal resistance was evaluated according to the following evaluation criteria. It should be noted that the measurement and evaluation of thermal resistance were performed in Examples 1-6 and Comparative Examples 1-3, but not in Examples 7-12 and Comparative Examples 4-7.
[0308] A: Thermal resistance less than 1.6m 2 ·K / W
[0309] B: Thermal resistance is 1.6m. 2 ·K / W or above
[0310] (Pulse NMR measurement)
[0311] 5.0 g of the cured resin compositions (thermally conductive materials) prepared in Examples 7-12 and Comparative Examples 4 and 6 were used as test samples. This sample was filled into a sample tube for pulse NMR measurement, and the temperature of the sample tube was adjusted to 10°C. The sample tube was then inserted into the main body of the measuring apparatus, and a holding time of 10 minutes was set for temperature stabilization. The T2 relaxation curve was measured under the following measurement conditions. It should be noted that pulse NMR measurement was not performed in Comparative Examples 5 and 7 because thermally conductive materials could not be prepared.
[0312] <Measurement Time>
[0313] Machine: Minispec MQ20
[0314] Temperature: 10dC
[0315] Environment: Air
[0316] Pulse sequence: Solid echo
[0317] Scans: 128
[0318] Recycle delay: 1 second
[0319] Pulse Separation: 0.64 μs
[0320] Numbers of points: 9369
[0321] <Parameters>
[0322] The obtained relaxation curve was fitted using the following fitting function, and a1 was obtained as a parameter.
[0323] The Weibull coefficients are fixed at W1 = 2, W2 = 2, and W3 = 1.
[0324] Fitting function: Three-parameter Weibull function
[0325] (The meanings of a1, a2, and a3 in the above fitting function are the same as those of a1~a3 in equation (12), x is the same as that of x in equation (12), and t is the same as that of t1~t3 in equation (12))
[0326] [Table 4]
[0327] It is evident that the resin compositions prepared in Examples 1-6, by comprising copolymer compounds that satisfy the requirements of the present invention, exhibit a large variation in elastic modulus, resulting in excellent workability and high-temperature compressibility. Furthermore, it is evident that the elongation provides excellent reprocessability. Moreover, it is evident that low exudation leads to high reliability, and low thermal resistance results in excellent thermal conductivity.
[0328] In contrast, the resin composition prepared in Comparative Example 1, by replacing the copolymer compound of the present invention with a compound that does not contain carbon-carbon double or triple bonds in the molecule, has a smaller elongation and does not exhibit excellent reprocessability.
[0329] Furthermore, the resin composition prepared in Comparative Example 2, by replacing the copolymer compound of the present invention with a commercially available compound that does not contain carbon-carbon double or triple bonds in its molecule, similarly to Comparative Example 1, exhibits reduced elongation and fails to demonstrate excellent reprocessability. Moreover, it has high thermal resistance and poor thermal conductivity.
[0330] The resin composition prepared in Comparative Example 3 contained no copolymer compounds at all. As a result, the workability and high-temperature compressibility were not excellent due to the small change in elastic modulus.
[0331] [Table 5]
[0332] Pulsed NMR measurements were performed on the thermally conductive materials prepared in Examples 7-12. The results showed that as the proportion of a1 increases, the elastic modulus changes significantly, resulting in excellent operability and high-temperature compressibility.
[0333] In contrast, pulsed NMR measurements were performed on the thermally conductive materials prepared in Comparative Examples 4 and 6. The results showed that as the proportion of a1 decreased, the elastic modulus changed little, resulting in poor operability and high-temperature compressibility.
[0334] Furthermore, in Comparative Examples 5 and 7, a large amount of PCM with poor compatibility with polyorganosiloxane (X) was mixed in, resulting in difficulty in mixing the components and making it impossible to produce thermally conductive materials.
[0335] Explanation of symbols
[0336] 21 Thermal Insulation Materials
[0337] 22 The copper block below
[0338] 23 The copper block above
[0339] 24 Heaters
[0340] 25 Heat sink
[0341] 26 Force Sensors
[0342] S test piece
[0343] θ j0 The temperature of the copper block above
[0344] θ j1 The temperature of the copper block below.
Claims
1. A copolymer compound having the structure shown in formula (1) below, In equation (1), X 1 ~X 3 Each is an independent trivalent organogroup, Y 1 ~Y 3 Each is an independent divalent organic group, Z 1 Z is a monovalent organic group. 2 R is a hydrogen atom or a monovalent organic group, R is an independent monovalent organic group, W is a divalent organic group and contains one or more carbon-carbon double or triple bonds, k is a number between 16 and 33, n, m, o, r, and s are each a number greater than 1, and p and q are each a number greater than 0.
2. The copolymer compound according to claim 1, wherein W comprises one or more 1,1-vinylidene or 1,2-vinylidene.
3. The copolymer compound according to claim 1 or 2, wherein X 1 ~X 3 It is a hydrocarbon group with 2 or more but less than 3 carbon atoms.
4. The copolymer compound according to claim 1 or 2, wherein the Y 1 ~Y 3 It contains ester or amide groups.
5. The copolymer compound according to claim 1 or 2, wherein m, n, and o satisfy the relationship of the following formula (α), m / (n+m+o)≥0.025 Formula (α).
6. The copolymer compound according to claim 1 or 2, wherein m, n, o, and r satisfy the relationship of the following formula (β), o r / (n+m+o)≥1.00 Equation (β).
7. A resin composition comprising the copolymer compound of claim 1 or 2, a polyorganosiloxane having hydrogen atoms in its molecular backbone that are directly bonded to silicon atoms, a catalyst, and a thermally conductive filler.
8. The resin composition according to claim 7, further comprising a polyorganosiloxane having carbon-carbon double bonds in its molecular backbone.
9. The resin composition according to claim 7, wherein the thermally conductive filler is selected from at least one of metals, inorganic hydroxides, inorganic oxides, inorganic nitrides, carbon fibers, graphite and diamond.
10. The resin composition according to claim 7, wherein the content of the copolymer compound is 10 parts by mass or more relative to 100 parts by mass of the polyorganosiloxane (X) contained in the resin composition.
11. A thermally conductive sheet, formed from a cured product of the resin composition of claim 7. The thickness of the thermally conductive sheet is 0.05 mm or more and 5 mm or less.
12. The thermally conductive sheet according to claim 11, wherein at least one of the thermally conductive fillers has an anisotropic shape. Furthermore, the thermally conductive filler having the anisotropic shape is oriented within the thermally conductive sheet.
13. A thermally conductive material comprising a polyorganosiloxane, a thermally softening compound, and a thermally conductive filler. When the T2 relaxation curve of the pulsed NMR obtained by measuring the thermally conductive material at 10°C using the solid-state echo method is analyzed using the least squares error fitting function shown in the following equation (12), the proportion of a1 obtained is more than 10%. In equation (12), a1, a2, and a3 are the intensity proportions of each relaxation component such that a1 + a2 + a3 = 100%. t1, t2, and t3 are the T2 relaxation times of each relaxation component, and t1 < t2 < t3. x represents the observation time in the relaxation measurement of pulsed NMR.
Citation Information
Patent Citations
JP1974054475A
Device for dispensing fixed-amount of adhesive
JP1989036035A
Phase change heat transfer material
JP2001089756A
Member for countermeasure against heat
JP2012102264A
Thermally conductive film
JP2023047991A